2D Outer Side Chain‐Incorporated Y Acceptors for Highly Efficient Organic Solar Cells with Nonhalogenated Solvent and Annealing‐Free Process. Issue 9 (6th July 2022) - Park, Jin Su; Sun, Cheng; Han, Yunghee; Kim, Geon-U; Phan, Tan Ngoc-Lan; Kim, Yun-Hi; Kim, Bumjoon J.
Abstract : To fabricate high‐performance organic solar cells (OSCs) by green solvent processing, it is essential to control the aggregation behavior and processability of constituent small‐molecule acceptors (SMAs). Herein, a series of SMAs (A1–A4) with enhanced aggregation behavior and processability is developed by replacing the linear alkyl outer side chains of BTP‐eC9 with 2D functional groups. The PM6:A1 SMA blend exhibits appropriate crystallinity, favorable blend morphology, superior electrical properties, and affords an OSC with a high power conversion efficiency (PCE) of 16.8%. Importantly, the OSC is fabricated using a nonhalogenated solvent ( ortho ‐xylene), annealing‐free process. In contrast, the reference PM6:BTP‐eC9‐based OSC exhibits a lower PCE of 15.3%. Structural analyses reveal that the 2D outer side chains of A1 induce steric hindrance between its dithienothiophen[3, 2‐b]‐pyrrolobenzothiadiazole (BTP) core and the 2‐(3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile end groups, optimizing its molecular planarity and aggregation property. It is further found that the SMAs with chlorinated IC end groups afford OSCs with higher PCEs than SMAs with fluorinated end groups. Abstract : Herein, the 2D outer side chain effects on the Y acceptors in terms of structural and aggregation properties, blend morphology, and organic solar cell (OSC) performance are investigated. High‐performance OSCs with 16.8% efficiency are achieved from the nonhalogenated solvent, annealing‐free fabrication process.